Ketamine antidepressant properties: a systematic review of clinical trials - Ferreira, Diogo (2022)
Ketamine has been used to provide a rapid and persistent antidepressant effect in patients with treatment-resistant depression. This drug reverses depressive symptoms by blocking N-methyl-D-Aspartate receptors, which causes a downstream effect on glutamatergic system. The main goal of this work consisted in a systematic review of the antidepressant and adverse events of Ketamine in patients with treatment-resistant depression. Keywords were defined with PICO´s strategy and systematic review was performed by using the PUBMED database. After inclusion and exclusion criteria, a total of 21 articles were included. Results showed a rapid antidepressant action from the resynchronization of neural circuits upon Ketamine use. However, this drug was also associated with several induced side-effects, including changes in blood pressure, dissociative symptoms, headache, nausea and vomits. Different routes of administration and ketamine metabolites may be used to help to overcome some of the induced side-effects.